Analysis Of Factors Affecting The Market Share Of Sharia Banking In Indonesia - Yose Triyurni Sandra (Tirtayasa Ekonomika, 2023)
This study aims to analyze the effect of inflation, economic growth, BI rate, and Capital Adequacy Ratio (CAR) on the market share of Islamic banking in Indonesia for the period 2015 - 2022. The data used is secondary data in the form of quarterly time series data. sourced from Indonesian Central Bank (BI), Statistics Central Bureau (BPS), and Indonesian Financial Authority (OJK). The method used is multiple linear regression and uses the SPSS 25 program. The results of this study indicate that partially the Inflation and Capital Adequacy Ratio (CAR) has a significant positive effect, and the BI rate variable has a significant negative effect on the market share of Islamic banking in Indonesia. Meanwhile, economic growth variables have no effect. Simultaneously, all independent variables have a significant influence on the market share of Islamic banking in Indonesia.